2010
DOI: 10.1021/ic101146e
|View full text |Cite
|
Sign up to set email alerts
|

Tiopronin Gold Nanoparticle Precursor Forms Aurophilic Ring Tetramer

Abstract: In the two step synthesis of thiolate-monolayer protected clusters (MPCs), the first step of the reaction is a mild reduction of gold(III) by thiols that generates gold(I) thiolate complexes as intermediates. Using tiopronin (Tio) as the thiol reductant, the characterization of the intermediate Au4Tio4 complex was accomplished with various analytical and structural techniques. Nuclear magnetic resonance (NMR), elemental analysis, thermogravimetric analysis (TGA), and matrix-assisted laser desorption/ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 57 publications
11
35
0
Order By: Relevance
“…The values we calculated for E inc and E av shown in Table 1 are in agreement with H€ akkinen, Gr€ onbeck, and co-workers. 6,8 Our cyclic clusters are also in agreement with experimentally known gold structures found by Bau, 2 Simpson et al, 9 LeBlanc et al, 10 In comparison, the PBE monomer fragmentation energies of the dimers are 1.17 eV for the cis configuration and 1.18 eV for the trans configuration. At the TPSS/TZP level of theory, these fragmentation energies are predicted to be 1.11 and 1.13 eV, respectively.…”
Section: ' Results and Discussionsupporting
confidence: 89%
“…The values we calculated for E inc and E av shown in Table 1 are in agreement with H€ akkinen, Gr€ onbeck, and co-workers. 6,8 Our cyclic clusters are also in agreement with experimentally known gold structures found by Bau, 2 Simpson et al, 9 LeBlanc et al, 10 In comparison, the PBE monomer fragmentation energies of the dimers are 1.17 eV for the cis configuration and 1.18 eV for the trans configuration. At the TPSS/TZP level of theory, these fragmentation energies are predicted to be 1.11 and 1.13 eV, respectively.…”
Section: ' Results and Discussionsupporting
confidence: 89%
“…Characterization of TPN-Au.-The broadened NMR spectrum and absorption at 340 nm in the UV-vis spectrum were appropriate for the polymeric TPN-Au that Simpson et al 20 characterized as a cyclic tetramer shown in Figure 1. Formation of the TPN-Au tetramer was confirmed by observation of the deprotonated molecular ion in the MALDI mass negative ion spectrum and molecular ion with 1-4 potassium atoms in the positive ion spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The particle diameter was consistent with gold nano-cluster formation by collapse of the tetramer ring. 20 By indirect observation, the 20-40 nm Au particles from the suspension could also selectively adhere to the modified COP surface sufficiently, allowing catalyst adsorption and adhesive electroless gold plating. Irradiation of PEN film also resulted in formation of a 30-40 nm deep oxygen rich modified layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater number of Au−S interactions in the 20AuMPG system is afforded by the smaller size and less bulky MPG ligand, resulting in a higher cumulative Au−S surface interaction area. 29 When comparing the size of the particles imaged by SEM, it is determined that the size of the 20AuBSA nanoparticles is 9.6 ± 2.3 nm ( Figure 1A,B), while the 20AuMPG nanoparticles are 4.7 ± 2.0 nm in size ( Figure 1C,D). The distribution statistics are based on thousands of particles from multiple SEM images of the same samples.…”
Section: ■ Introductionmentioning
confidence: 99%